Poultry food products—a source of avian influenza virus transmission to humans?. (February 2016) - Harder, T.C.; Buda, S.; Hengel, H.; Beer, M.; Mettenleiter, T.C.
Abstract: Global human mobility and intercontinental connectivity, expansion of livestock production and encroachment of wildlife habitats by invasive agricultural land use contribute to shape the complexity of influenza epidemiology. The OneHealth approach integrates these and further elements into considerations to improve disease control and prevention. Food of animal origin for human consumption is another integral aspect; if produced from infected livestock such items may act as vehicles of spread of animal pathogens, and, in case of zoonotic agents, as a potential human health hazard. Notifiable zoonotic avian influenza viruses (AIV) have become entrenched in poultry populations in several Asian and northern African countries since 2003. Highly pathogenic (HP) AIV (e.g. H5N1) cause extensive poultry mortality and severe economic losses. HPAIV and low pathogenic AIV (e.g. H7N9) with zoonotic propensities pose risks for human health. More than 1500 human cases of AIV infection have been reported, mainly from regions with endemically infected poultry. Intense human exposure to AIV-infected poultry, e.g. during rearing, slaughtering or processing of poultry, is a major risk factor for acquiring AIV infection. In contrast, human infections through consumption of AIV-contaminated food have not been substantiated. Heating poultry products according to kitchen standards (core temperatures ≥70°C, ≥10 s) rapidly inactivates AIV infectivity and renders fully cooked products safe. Nevertheless, concerted efforts must ensure that poultry products potentially contaminated with zoonotic AIV do not reach the food chain. Stringent and sustained OneHealth measures are required to better control and eventually eradicate, HPAIV from endemic regions.